Analysis of the Impact of the Ban on Cellphone Use: Implications on Students’ Learning Focus, Social Relationships and Educational Communication - Rezza Ardiansyah; Meilia Rosani; Mulyadi Mulyadi (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2026)
This qualitative study examines the impact of a mobile phone ban at SMAN 6 Prabumulih, Indonesia, on students’ learning focus, social relationships, and educational communication. Data were collected through semi-structured interviews with 10 stakeholders (principal, teachers, students, staff), observations, and document analysis. Findings indicate that the ban significantly improved classroom concentration, fostered face-to-face interactions, and reduced digital misconduct. However, challenges included enforcement difficulties, limited urgent communication, and reduced access to digital learning tools. The study highlights the need for balanced policies that restrict disruptive use while supporting educational technology integration. The school also takes strategic steps, such as implementing the 5S Movement and providing formal communication channels through homeroom teachers and administration, to ensure that the relationship between students, teachers, and parents is maintained well. Overall, this policy fosters a learning environment that prioritizes humaneness, collaboration, and character development.